2010
DOI: 10.1038/cmi.2010.51
|View full text |Cite
|
Sign up to set email alerts
|

Role of dendritic cells: a step forward for the hygiene hypothesis

Abstract: The hygiene hypothesis was proposed more than two decades ago, but its mechanism remains unclear. This review focuses on recent advances in the field, especially on the role played by dendritic cells (DCs) and their modulating effects on various infections and allergic diseases, including allergic asthma. DCs isolated from mice long after the resolution of an infection were reported to have a significant modulating effect on allergen-specific Th2 responses in both in vitro and in vivo systems. These DCs showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 110 publications
(149 reference statements)
1
19
0
Order By: Relevance
“…Early infections seem to shape the immune system as compared with more recent illnesses [54]. One answer as to why some classically Th2-skewing parasites induce atopy and others do not is via their ability to induce Treg or another type of IL-10/TGFb-producing cell [55,56].…”
Section: Mechanism and T-regulatory Cellsmentioning
confidence: 99%
“…Early infections seem to shape the immune system as compared with more recent illnesses [54]. One answer as to why some classically Th2-skewing parasites induce atopy and others do not is via their ability to induce Treg or another type of IL-10/TGFb-producing cell [55,56].…”
Section: Mechanism and T-regulatory Cellsmentioning
confidence: 99%
“…15 Given the above data demonstrating that the liver-draining LNs are vital unclear. In our study, we identified the liver-draining LNs by injection of Evans blue, demonstrating staining of the portal LN by Evans blue at 5 min post-injection and the celiac LN at 8 min (Figure 2a).…”
Section: Induction Of Anti-hbv Responses In the Liver-draining Lnsmentioning
confidence: 99%
“…T helper (T H ) cells such as T H 1, T H 2, T H 17, T reg and antigen-presenting cells (APC), e.g., dendritic cells, monocytes and macrophages [36]. Chronic inflammation involves the differential polarization of T H cells.…”
Section: Immune Modulation Of Inflammatory Pathologiesmentioning
confidence: 99%
“…Naïve T H cell activation and polarization into the different subtypes occur in response to at least three stimuli, namely presentation of antigen by APC, co-stimulatory molecules and the cytokine milieu [37]. T H 1 (type 1 immunity against intracellular pathogens such as viruses and cancer cells) relies on IFNc, IL2, IL12 (major T H 1 polarizing cytokines), and T H 2 (type 2 immunity against extracellular pathogens such as multi-cellular parasites) relies on IL4, IL5 [36]. T reg is crucial for suppressing excessive immune responses [38].…”
Section: Immune Modulation Of Inflammatory Pathologiesmentioning
confidence: 99%